Akuntabilitas dalam Perspektif Ajaran Karma Phala Sebagai Pedoman Untuk Membangun Karakter Auditor - Munidewi, Ida Ayu Budhananda (Jurnal Ilmiah Akuntansi dan Bisnis, 2017)
Auditor’s accountability consists of aspects such as motivation, social obligations and dedication to profession. These three aspects must be owned by the auditor to be able to produce a good audit quality.Hindu’s society recognize the legal doctrine of karma phala or causal. Due to the reason, this purpose study is to examine the accountability of auditors in the perspective of karma phala. This study used a qualitative method that focuses on the descriptive and the interpretative of human behaviour. The research data was obtained through participant observation and unstructured interview. Data analyze through three stages: data reduction, data presentation and conclusion. The result shows that karma phala actually been embedded in every aspect of auditor’s accountability, but need more emphasis on awareness of the role of auditors in the public and the profession.
Keywords: Akuntabilitas auditor, hukum karma phala, karakter auditor